African Provinces under Roman Exploitation: The Agricultural Aspect as a Model - silhadi, dehbia (The Algerian Historical Journal, 2026)
Economic potential was available in Ancient Maghreb that helped achieve economic stability for the Roman Empire. Upon their contact with African territory, the Romans discovered the agricultural importance of the ancient Maghreb lands and became familiar with the region's varied wealth. Through extensive land exploitation and efforts to intensify agricultural production using particular strategies, they aimed to address the increasing demands of Roman society and serve political purposes. Through this research, we focus on the Roman agricultural exploitation in the African provinces (as Proconsularis and Numidia) during the reign of the first emperor.